Work done at Kansas State University in support of the muon-to-electron conversion experiment (Mu2e) - Tyner, Jo Lynn (Kansas State University, 2023)
The Muon-to-Electron Conversion Experiment (Mu2e) located at Fermi National Accelerator Laboratory (FNAL) is an exciting probe into the Intensity frontier of modern particle physics. It aims to study charged lepton flavor violation (CLFV), a rare process that has never yet been observed experimentally, with a single event sensitivity of 2.87 × 10ˉ¹⁷ [1]. Because this target sensitivity is so high, extensive background elimination is required to achieve it. Cosmic rays are a significant contribution to the background. Therefore, the Cosmic Ray Veto system was developed for Mu2e. If cosmic ray muons capable of producing false CLFV signals in the detection apparatuses are detected in the veto system, the data from the time period during which this particle traverses the detector will be vetoed or deleted. The Cosmic Ray Veto system (CRV) aims to help eliminate cosmic ray background while minimizing detector dead time. The Mu2e team is comprised of hundreds of scientists from around the world, including a team located at Kansas State University (K-State). In this work, I will give a brief description of the experiment, explore the software and hardware central to its mission, and describe the work done at Kansas State to support this endeavor. I will also prompt future studies that can be completed at K-State to further the mission of the Mu2e team.
Keywords: High energy physics experiments; Muon to electron conversion experiment; Cosmic ray veto; Neutrino experiments